2006
DOI: 10.1682/jrrd.2005.04.0066
|View full text |Cite
|
Sign up to set email alerts
|

Using cranial electrotherapy stimulation to treat pain associated with spinal cord injury

Abstract: Abstract-Treatments for chronic pain in persons with spinal cord injury (SCI) have been less than effective. Cranial electrotherapy stimulation (CES), a noninvasive technique that delivers a microcurrent to the brain via ear clip electrodes, has been shown to effectively treat several neurological and psychiatric disorders. The present study examined the effects of daily 1-hour active CES or sham CES treatment (randomly assigned) for 21 days on pain intensity and interference with activities in 38 males with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…In a pilot study, Tan et al 85 examined the effects of daily 1-hour treatment for 21 days on pain intensity and interference with activities in 38 male patients with SCI who were randomized to receive active CES (n = 18) or sham CES (n = 20). The active CES group reported significantly decreased daily pain intensity and pain interference compared with the sham CES group.…”
Section: Cranial Electrotherapy Stimulationmentioning
confidence: 99%
“…In a pilot study, Tan et al 85 examined the effects of daily 1-hour treatment for 21 days on pain intensity and interference with activities in 38 male patients with SCI who were randomized to receive active CES (n = 18) or sham CES (n = 20). The active CES group reported significantly decreased daily pain intensity and pain interference compared with the sham CES group.…”
Section: Cranial Electrotherapy Stimulationmentioning
confidence: 99%
“…There have been reports of slight irritation at the electrode sites [39], burns at the electrode site [47], slight dizziness [43], headache [48], giddiness [48], and tooth pain [48]. In a recent study, Tan et al found CES to be effective in relieving musculoskeletal and neuropathic pain in persons with spinal cord injury (SCI) [49]. Not only was there a significant difference in the decrease in pain from before to after daily sessions between those who received active CES versus those who received sham CES, but also there was a significant change in pain interference with several quality-of-life domains from pre- to postintervention.…”
Section: Introductionmentioning
confidence: 99%
“…This burden can create an added risk for psychological morbidity 8,11,12 and reduced well-being, [13][14][15][16] and also place significant limitations on physical and social functioning. 4,17 Research shows that pharmacological, 16,18 nonpharmacological, [19][20][21] and psychological [22][23][24] treatments of chronic pain can provide some relief for some individuals with physical disabilities. However, all of the available treatments have limitations, which include (1) a lack of meaningful efficacy for the majority of individuals, (2) absence of evidence for long-term beneficial effects, (3) high costs, and (4) for some treatments, significant side effects.…”
mentioning
confidence: 99%